1999
DOI: 10.1007/s001340050788
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous intracerebral hemorrhage in critically ill patients: incidence over six years and associated factors

Abstract: Spontaneous nonhypertensive ICH is a rare, fatal event in the ICU. Associated factors include thrombocytopenia, the need for mechanical ventilation, elevated PIP and PaCO2, sepsis, and impaired hepatic and renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…Type and acuity of illness as well as presence of fever, sepsis, multiple organ failure, coagulopathy, medication, and platelet function have to be evaluated. Thus, hypertension and sepsis are frequently associated in patients with intracerebral hemorrhage after liver transplantation [2,24], as in critically ill patients [26].…”
Section: Discussionmentioning
confidence: 99%
“…Type and acuity of illness as well as presence of fever, sepsis, multiple organ failure, coagulopathy, medication, and platelet function have to be evaluated. Thus, hypertension and sepsis are frequently associated in patients with intracerebral hemorrhage after liver transplantation [2,24], as in critically ill patients [26].…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Patients with DIC and a platelet count of <50x10 9 /l have a 4 to 5-fold higher risk for bleeding as compared to patients with a higher platelet count. [10][11][12] More common is the occurrence of thrombosis in small and midsize vessels contributing to organ failure in patients with DIC, with reported ranges from 10-15% in patients with cancer or trauma up to 40% in patients with sepsis, although these estimates may not be very precise. 13,14 A variety of organs in patients with DIC show intravascular fibrin deposition at pathological examination related to the clinical dysfunction of the organs.…”
Section: Introductionmentioning
confidence: 99%
“…Serious adverse bleeding events in randomized trials occurred at consistently low rates. Moreover, the incidence of intracranial hemorrhage across all studies is comparable to the rate of spontaneous intracranial hemorrhage observed in critically ill patients [ 21 ]. The risk for bleeding can be mitigated by following package inserts (approved labeling) and avoiding off-label use (in contraindicated patients).…”
Section: Safetymentioning
confidence: 85%